Coarse Marbled Beef is Juicier and More Flavorful Than Fine or Medium Marbled Beef - K. R. Vierck; J. M. Gonzalez; T. A. Houser; E. A. Boyle; T. G. O'Quinn (Kansas Agricultural Experiment Station Research Reports, 2017)
Beef palatability and eating experience is driven primarily by U.S. Department of Agriculture quality grade and marbling levels. Beef USDA quality grade consists of both marbling levels and maturity. Conventionally, marbling texture has not been a consideration of quality grades. Currently, only one study has assessed the effects of marbling texture on beef palatability. Despite this, preferences for fine or medium marbling exist with both packers and retailers, as approximately 75% of branded beef programs under the supervision of USDA-AMS require fine or medium textured marbling, which equates to losses of premiums for packers and producers (USDA, 2016). The objective of the study was to evaluate the effects of marbling texture on trained sensory panel ratings of beef strip loin steaks of varying USDA quality grades and marbling textures.
Keywords: marbling; palatability; trained sensory panel